POSHAN's abstract digest on maternal and child nutrition research - Issue 29 - Avula, Rasmi (International Food Policy Research Institute, 2019)
In this issue of Abstract Digest, we present to you a collection of articles on various outcomes, determinants and interventions related to maternal and child nutrition, from around the world and India, in particular. Additionally, articles from three special issues including BMJ Global Health’s supplement on the measurement of reproductive, maternal, newborn and child health and nutrition, Maternal & Child Nutrition’s supplement on the marketing and consumption of commercial foods fed to young children in low and middle‐income countries, and the Annals of the New York Academy of Sciences’ special issue on the risk of excessive intake of vitamins and minerals are featured in this issue.